PERENCANAAN SISTEM JARINGAN TAMBAK GARAM DI PEMONGKONG KABUPATEN LOMBOK TIMUR - Rano Adiyoso; Ricky Darmawan; Abdul Kadir; Hari Nugroho (Jurnal Karya Teknik Sipil, 2014)
Jerowaru Pemongkong village district of East Lombok, West Nusa Tenggara is one of the salt producing areas. Water systems that do not meet the technical standards causing the low production of salt. In efforts to increase production and quality, a need to increase salt production system by using a standard technical planning. In this plan, the planning standards used are salt production system in Korea is the ratio of the reservoir : evaporation area : crystallization area = 55 : 30 : 15, a water supply system with pumping and other buildings such as intake planning, channel and floodgates that refer to the Technical Irrigation Planning Standards. At the beginning of the planning is done making salt ponds plot layout, plan continued with dimensions and elevation intake structure, reservoir, evaporation area, crystallization area and the channel of a water carrier, so that the water supply can be guaranteed. From the study sites were sampled an area of 10.79 ha, gained 5.39 ha of reservoir, 3.24 ha of evaporation area and 1.62 ha of crystallization area. According to the criteria of the salt pond water depth according to the Ministry of Marine Affairs and Fisheries of the Republic of Indonesia, the water level in the reservoir is 50 cm, the water level in evaporation area is 30 cm, and the water level in crystallization area is 5 cm. The discharge of primary channel is 0,526 m3/sec, obtained from the analysis of the primary channel dimensions B = 1.50 m,  H = 0.75 m, while the discharge of secondary channel is 0.213 m3/sec, obtained from the analysis of channel dimensions secondary B = 1.00 m, H = 0.50 m. Discharge plan on the culvert at 0.669 m3/sec, obtained from the analysis of the culvert dimensions 1.50 m x 1.50 m. To maintain water supply continuity water pumps were used with capacity of 98.57 liters/sec. By using this system is expected to increase the productivity of salt + 90 tons/ha/year to + 150 tons/ha/year. The cost of manufacture new salt ponds in this area ranges from + Rp . 165,000,000.00 / ha.